The adsorption of 1,3-butadiene on Pd/Ni multilayers: The interplay between spin polarization and chemisorption strength - Gómez, Guillermina (2010)
The adsorption of 1,3-butadiene (BD) on the Pd/Ni(1 1 1) multilayers has been studied using the VASP method in the framework of the density functional theory (DFT). The adsorption on two different configurations of the Pd n/Nim(1 1 1) systems were considered. The most stable adsorption sites are dependent on the substrate composition and on the inclusion or not of spin polarization. On Pd1Ni3(1 1 1) surface, diπcis and 1,2,3,4-tetra-σ adsorption structures are the most stable for non-spin polarized (NSP) and spin polarized (SP) levels of calculation, respectively. Conversely, on Pd3Ni1(1 1 1) surface, the 1,2,3,4-tetra-σ adsorption structure is the most stable for both NSP and SP levels, respectively. The magnetization of the Pd atoms strongly modifies the adsorption energy of BD and its most stable adsorption mode. On the other hand, as a consequence of BD adsorption, the Pd magnetization decreases. The smaller adsorption energies of BD and 1-butene on the Pd1Ni3(1 1 1) surface than on Pd(1 1 1) can be associated to the strained Pd overlayer deposited on Ni(1 1 1).